Bermudagrass Cultivars with Different Tolerance to Nematode Damage Are Characterized by Distinct Fungal but Similar Bacterial and Archaeal Microbiomes - Chang Jae Choi; Jacqueline Valiente; Marco Schiavon; Braham Dhillon; William T. Crow; Ulrich Stingl (Microorganisms, 2022)
Turfgrass landscapes have expanded rapidly in recent decades and are a major vegetation type in urbanizing ecosystems. While turfgrass areas provide numerous ecosystem services in urban environments, ecological side effects from intensive management are raising concerns regarding their sustainability. One potentially promising approach to ameliorate the ecological impact and decrease the use of agricultural chemicals is to take advantage of naturally evolved turfgrass-associated microbes by harnessing beneficial services provided by microbiomes. Unfortunately, especially compared to agricultural crops, the microbiomes of turfgrasses are not well understood. Here, we analyzed microbial communities inhabiting the leaf and root endospheres as well as soil in two bermudagrass cultivars, ‘Latitude 36’ and ‘TifTuf’, which exhibit distinct tolerance to nematode damage, with the goal of identifying potential differences in the microbiomes that might explain their distinct phenotype. We used 16S rRNA gene V4 and ITS2 amplicon sequencing to characterize the microbiomes in combination with microbial cultivation efforts to identify potentially beneficial endophytic fungi and bacteria. Our results show that Latitude 36 and TifTuf showed markedly different fungal microbiomes, each harboring unique taxa from Ascomycota and Glomeromycota, respectively. In contrast, less difference was observed from bacterial and archaeal microbiomes, which were dominated by Bacteroidetes and Thaumarchaeota, respectively. The TifTuf microbiomes exhibited lower microbial diversity compared to Latitude 36. Many sequences could not be classified to a higher taxonomic resolution, indicating a relatively high abundance of hitherto undescribed microorganisms. Our results provide new insights into the structure and composition of turfgrass microbiomes but also raise important questions regarding the functional attributes of key taxa.